SINTESIS MISTIK DALAM KEPEMIMPINAN POLITIK JAWA - Chalik, Abdul (Jurnal Review Politik, 2015)
This article discusses the social, cultural and religious social Javanese society and its impact on the political leadership. In general, the Javanese culture are described in their everyday lives at home, in the community in a variety of routine activities. Described in the Java community's daily behavior carefully, polite-spoken, introverted and promote harmony. It can not be separated from the philosophy of the Java community as well as the values of mystical-spiritual that comes from the teachings of religion, especially Hinduism and Islam. The relationship between philosophy of life with religious practices that they believe gave birth to the mystical synthesis, namely social behavior nuanced mystical. In real life can be found in all social spaces. Such practices also have implications for the style of community leadership in the public sphere. Where the cultural aspects and mystical impact on the way people act in public space